PERANCANGAN BUKU POP UP SEBAGAI MEDIA EDUKASI PEMBUATAN BATIK TULIS INDONESIA - Fairliantina, Edvin; Amalia, Aida Syahrani (Balitbangda Provinsi Lampung, 2019)
Batik as a cultural heritage of the Indonesian nation that has been passed down since ancient times, has a very important role in the journey of the Indonesian nation. Batik producers are spread across almost every region of Indonesia with their own motifs and characteristics. The research method uses research and development with a descriptive approach. Data collection techniques through observation and literature studies Conclusion: (1) This pop-up book provides accurate and comprehensive information about the manufacturing process. (2) This design uses storyboards, moodboards, illustrations, motion graphics, typography, and colors so that the use of visual elements is appropriate in supporting the design of pop-up books as educational media for making Indonesian batik. (3) The design produces the main media of the front cover, back cover, a glimpse of batik, the author's profile, and a pop-up book about making batik. (4) The design of supporting media produces Bookmarks, pins, Stickers, Notebooks, and batik with snakes and ladders characteristics